ANALISIS PENAMBAHAN NANO-REINFORCEMENT BERBASIS LIMBAH INDUSTRI TERHADAP KETAHANAN AUS DAN FATIGUE METAL MATRIX COMPOSITE BERBASIS DATA : BIBLIOMETRIC ANALYSIS - Nasution, Rafa Adhitya Dharmawangsa; Lubis, Hasyim Fadillah; M Ridho Rahman HSB (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
This study aims to analyze the research development related to the addition of industrial waste-based nano-reinforcements on the wear and fatigue resistance of metal matrix composites (MMC) through a bibliometric approach. Data were obtained from the Scopus database covering the years 2022–2025, limited to the Engineering subject area, Article document type, and English language. A total of 471 publications were analyzed using VOSviewer and SciMAT software to identify research trends, scientific collaborations, and dominant thematic clusters in this field. The results indicate a significant increase in publication numbers each year, reflecting growing attention toward sustainable composite materials. Keyword mapping visualization revealed five major clusters focusing on tribological property enhancement, graphene-based and cellulose-based nanofillers, and fabrication processes through powder metallurgy. Thematic mapping positioned reinforcement, tensile strength, and metallic matrix composites as motor themes driving this research domain. Overall, the findings emphasize that utilizing industrial waste as a nano-reinforcement material holds great potential to support the development of green MMCs with improved wear and fatigue resistance, illustrating a global research direction toward eco-friendly and resource-efficient materials.